"Learning lords" and "ink in your stomach": eliciting Chinese EFL students' beliefs about classroom participation. Issue 2 (2nd April 2020) - Girardelli, Davide; Kelly, Stephanie; Chen, Bodong; Zhou, Xiaogao; Gu, Tingting
ABSTRACT: Drawing from the theory of planned behavior, we conducted a belief elicitation study to gain insights on what considerations guide Chinese English-as-foreign-language students' decision to participate in English during class. We used four semistructured focus groups (in Chinese) to explore salient beliefs from a total of 34 Chinese university students enrolled in a Sino-American international branch campus. Results suggest that participants considered attentive listening as an integral part of their decisions about classroom participation, probably given their precollege education experience. They also perceived participation to be an effective means to improve English skills and to acquire a Western mindset, but also a frustrating practice that can waste class time and generate anxiety. Finally, through verbal and nonverbal communication, both instructors and classmates played a crucial role in affecting these students' intention to participate in English during class. Ultimately, we discuss practical pedagogical implications as well as relevant theoretical implications.